The role of voluntary accounting disclosure in enhancing information confidence in (Journal of Accounting and Financial Studies ( JAFS ), 2021)
ABSTRACT:The study aimed to identify the impact of the role of voluntary accounting disclosure in enhancing confidence in the informational content of financial reports. Correlation - Spearman to measure the degree of correlation, as well as the method of simple linear regression analysis, and the study reached several results, including: The level of enhancing the information content in the annual financial reports of the Palestinian banks listed on the Palestine Exchange under study reached the overall average (total) (94.1%), and also Voluntary Accounting Disclosure in Enhancing Confidence in the Informational Content of the List of Change in Ownership Equity of Listed Banks in Palestine and explains what is (35.2%) of the change in it.The study recommended encouraging the sector of banks listed on the Palestine Stock Exchange with more interest in disclosing optional information because of its importance to stakeholders and because it increases confidence in the published financial reports. Financial and non-financial, whether about the current or future situation.Key words: Optional Disclosure, Financial Reports, Palestine Stock Exchange.